1997
DOI: 10.1111/j.1525-1470.1997.tb00981.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidermolysis Bullosa Associated with Congenital Localized Absence of Skin, Fetal Abdominal Mass, and Pyloric Atresia**

Abstract: A 2320-g male infant was delivered at 35 weeks gestation to a mother who had polyhydramnios. He had a combination of congenital localized absence of skin, unilateral hydronephrosis, and hydroureter due to ureterovesical obstruction, and nonbilious vomiting due to pyloric atresia. Blistering of the skin developed after birth. Epidermolysis bullosa simplex was confirmed by electron microscopy of a skin biopsy specimen. We describe this patient, who had three unusual manifestations of epidermolysis bullosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 22 publications
2
20
1
Order By: Relevance
“…This patient died at 20 days of age from skin infection leading to staphylococcal sepsis and respiratory failure. 58 Another patient with skin blistering and pyloric atresia that was corrected shortly after birth had history of growth retardation, multiple urinary tract infections caused by bilateral grade 2 vesiculoureteral reflux, and chronic renal insufficiency by 3 years of age. She underwent bilateral ureteral reimplantation and was found to have severely fibrosed ureters and multiple bullae involving her bladder epithelium.…”
Section: Renal and Vesicourinary Tract Involvement In Eb-pamentioning
confidence: 99%
“…This patient died at 20 days of age from skin infection leading to staphylococcal sepsis and respiratory failure. 58 Another patient with skin blistering and pyloric atresia that was corrected shortly after birth had history of growth retardation, multiple urinary tract infections caused by bilateral grade 2 vesiculoureteral reflux, and chronic renal insufficiency by 3 years of age. She underwent bilateral ureteral reimplantation and was found to have severely fibrosed ureters and multiple bullae involving her bladder epithelium.…”
Section: Renal and Vesicourinary Tract Involvement In Eb-pamentioning
confidence: 99%
“…These blisters most commonly appear at sites of friction and minor trauma such as the feet and hands but may occur in any other part of the body including internal organs, such as the esophagus, stomach and respiratory tract, without any apparent friction [2,8]. Extracutaneous manifestations include anemia, growth retardation, caries, enamel hypoplasia, gastrointestinal complications including pyloric stenosis, ocular erosion, pseudodactyly, as well as respiratory tract complications including laryngotracheal stenosis or stricture [2,8].…”
Section: Discussionmentioning
confidence: 99%
“…2016;5(1):9-12 squamous cell carcinoma with 80% metastases and death [2,8]. Tracheolaryngeal stenosis or stricture is the most significant ENT complication which may result in death from airway obstruction [9,10].…”
Section: Epidermolysis Bullosamentioning
confidence: 99%
See 1 more Smart Citation
“…Atrophic scarring, hypoplastic teeth and dystrophic nails all have been reported. [22] EB progressiva is another rare form of JEB characterized by progressive atrophic changes leading to early loss of finger print patterns and mild finger contractures. Electron microscopy studies have shown a normal dermo--epidermal junction zone, including normal hemidesmosomes.…”
Section: Clinical Subtypes Of Junctional Epidermolysis Bullosamentioning
confidence: 99%